Doped ferrites and their role on the production of hydrogen through thermochemical redox cycles [Resumo] - Furtado, Olívia (2020)
ABSTRACT: The thermochemical storage of solar energy is a method to store high energy densities in the form of chemical bonds, requiring only small amounts of material to store large amounts of energy. Metal oxides are promising materials to produce hydrogen from thermochemical cycles, being an environmentally friendly and sustainable option.